The Role Of Democratic Leadership In Enhancing Human Capital - ديب كندة (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of the research is to determine the role that the democratic leadership style plays as the best leadership style compared to the authoritarian and permissive leadership styles, in enhancing human capital in universities, by applying it to the administrative workers at Tishreen University. The research was based on the descriptive and analytical approach, and the research community included all the administrative workers at Tishreen University. As for the research sample, it is a soft sample of (150) administrative workers. With a response rate of (92.67%). The results showed that there is a strong positive correlation with significant significant between the democratic leadership style and the dimensions of human capital development (skills, experience, knowledge, training) of Tishreen University employees.